Fungos anemófilos de Manaus - Fonseca, Ozório José de Menezes; Conceição, Lucia Alves (Acta Amazonica, 1977)
Results of a survey of the airborn fungi in Manaus, State of Amazonas, Brazil, are presented. Samples were taken from two different localities of this city during the months of September 1975 through August 1976. The findings are presented in coordination with the seasonal climatological variations and compared with similar studies carried out in other cities of Brazil.